Brand experience, brand identity are influential towards brand loyalty with mediation of brand love and brand trust - Prastiwi, Estik Hari; Cempena, Ida Bagus; Barata, Fausta Ari; Kartini, Ida Ayu Nuh (Edelweiss Applied Science and Technology, 2025)
This study aims to prove the influence of brand experience and brand identity on brand loyalty with the mediation of brand love and brand trust. This research design is a quantitative study using Warp PLS as a data Analysis tool. Warpl PlS data analysis with the outer model shows the validity and reliability of the model has met the criteria. Data analysis using the inner model has met the criteria. The results of the study show that brand experience has a significant effect on brand loyalty. Brand experience has a significant effect on brand love. Brand experience also has a significant effect on brand trust. Furthermore, brand love has a significant effect on brand loyalty. However, brand Identity has no significant effect on brand loyalty. Meanwhile, brand Identity has a significant effect on brand love. But brand Identity also has a significant effect on brand trust. Brand trust has a significant effect on brand loyalty. The conclusion from the results of this study is that brand experience directly or indirectly affects brand Loyalty, but brand identity directly does not have a significant effect on brand loyalty. Brand identity has a significant effect on brand loyalty with the mediation of brand love and brand trust. Practical implications of this study are that brand loyalty of food products with halal labels, namely KFC and MDc, is influenced by brand experience, brand love, and brand trust.